Stages of change for physical activity in adults from Southern Brazil: a population-based survey - Dumith, Samuel C (BioMed Central, 2007)
BACKGROUND: There is evidence that physical activity (PA) interventions tailored to individual's stages of change (SoC) are more effective in promote behavior change than "one-size-fits-all" interventions. However, only a few researches have investigated these stages towards PA behavior in representative samples of the population. Thus, the purpose of this study was to determine the prevalence and factors associated with the SoC for PA in a probabilistic sample of adults aged 20 years or over. METHODS: A population-based survey was undertaken in Pelotas, Southern Brazil, in 2005. An algorithm was applied to evaluate the SoC for PA, and PA was defined as being engaged in moderate-to-vigorous PA for at least 20 minutes on three times per week. The covariates collected in the questionnaire were: sex, age, skin color, marital status, education level, economic status, family income, smoking, body mass index (BMI) and self-reported health status. Data analyses were performed through Poisson and multinomial regression, taking the sampling design into account. RESULTS: Face-to-face interviews were applied to 3136 individuals, corresponding to a response rate of 93.5%. The prevalence across the stages was as follows: 38.3% in precontemplation, 13.0% in contemplation, 19.5% in preparation, 5.2% in action and 24.0% in maintenance. The elderly, married, smokers, and those with lower socioeconomic status were less likely to adopt, initiate and maintain regular PA. CONCLUSION: Despite the all benefits of PA, a high proportion of adults from Southern Brazil are physically inactive and do not present intention to engage in regular PA. The profile of those who are inactive but intend to do PA resembles those who are physically active. The findings of the present study can contribute to improve health behaviors and to plan health promotion strategies aimed at increasing the level of PA in the community.